TEACHING ARABIC SPEAKING IN AN ARTIFICIAL ENVIRONMENT (A DESCRIPTIVE STUDY TO BENEFIT FROM THE PROCESS OF TEACHING THE SKILL OF SPEAKING THE ARABIC LANGUAGE IN INDONESIA): تعليم الكلام اللغة العربية في البيئة الاصطناعية (دراسة تحليلية الوصفية لإستفادة عملية تعليم مهارة الكلام اللغة العربية في إندونيسيا) - Muhammad Ainul Yaqin (Fashohah : Jurnal Ilmiah Pendidikan Bahasa Arab, 2023)
The purpose of this study was to find out the theoretical basis for creating an artificial environment to develop Arabic speaking skills for non-Arabic speakers living in Indonesia. The method used is a literature review, where this study explores and connects existing theories with the subject matter of creating an Arabic-language environment in an artificial environment for non-Arabic speakers. As for the results of this study learning to speak Arabic for non-Arabic speakers is a diverse process because each student has a connection with the process of their learning activities in learning, in this case the relationship with the effectiveness of students and their background abilities. Usually students easily understand how irritation occurs from the outside, because they get their five senses, both sight, hearing, smell, taste, and touch. The process of teaching speaking to non-Arabic speakers at this school is divided into two parts: 1) inside the classroom, 2) outside the classroom. Key words: Arabic language learning; artificial environment.